Rancang Bangun Aplikasi Laundry Berbasis Website Pada Toko Dila Laundry di Pidie Jaya - Jamal, Aldi Yusri; , Baihaqi (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
In this millennial era, the rapid advancement of information technology has significantly influenced various sectors, including service-based businesses such as laundry services. Speed and accuracy in accessing information are now essential, thus requiring adequate technological support. Dila Laundry is a business operating in the laundry service industry that currently still relies on manual processes. Based on recent observations, the business does not yet utilize an integrated information system, and all customer and transaction data are still recorded manually in physical books. This lack of a digital system results in limited access to real-time information for customers, and some experience difficulties in dropping off or picking up their laundry due to busy schedules. To overcome these challenges, a web-based application is proposed to enhance Dila Laundry’s operations. This system is expected to provide customers with up-to-date information about available services, offer a reliable pick-up and delivery feature, streamline financial reporting, and improve service quality overall. By implementing this application, the business can operate more efficiently, minimize errors, and provide a more professional and convenient experience for its customers.